Registration of conversion electrons in a wide energy range by the detecting system “Si planar detector - metal Gd converter” - Bochek, G.L.; Kapliy, А.A.; Kiprich, S.K.; Kovalenko, G.D.; Maslov, N.I.; Ovchinnik, V.D.; Potin, S.M.; Semisalov, I.L.; Shlyahov, I.N.; Shulika, M.Yu.; Vasiliev, G.P.; Yalovenko, V.I. (Problems of Atomic Science and Technology, 2022)
The possibility of conversion electrons registration in a wide energy range by the detecting system “planar uncooled silicon detector – metal gadolinium converter” is studied. Research samples of detecting modules have been developed and manufactured. The spectrometric system for registration the energy levels of conversion electrons has been modernized. For the first time all levels of conversion electrons were experimentally registered in the energy range 30…200 keV by the detection “silicon planar detector – metal gadolinium converter”. Досліджено можливість реєстрації конверсійних електронів у широкому діапазоні енергій детектуючою системою “планарний кремнієвий неохолоджуваний детектор – металевий гадолінієвий конвертер”. Розроблено та виготовлено дослідницькі зразки детектуючих модулів. Модернізовано спектрометричну систему для реєстрації енергетичних рівнів конверсійних електронів. Вперше експериментально зареєстровані всі рівні конверсійних електронів у діапазоні енергій 30…200 кеВ детектуючою системою “кремнієвий планарний детектор – металевий гадолінієвий конвертeр”.